The real effects of financial technology: Marketplace lending and personal bankruptcy - Danisewicz, Piotr; Elard, Ilaf (Journal of Banking & Finance, 2023)
We examine how financial technology affects households in terms of personal bankruptcy by leveraging exogenous variation in marketplace credit supply to Connecticut and New York residents. We document a persistent rise in bankruptcies in the affected states following sharp decreases in marketplace lending, particularly among low-income households and in areas where marketplace loans for financing medical bills are severely rationed. Borrowers’ indebtedness or local economic conditions do not explain the results. The supply of other consumer credit by banks and finance companies remains unaffected, suggesting that the observed increase in bankruptcies arises principally from reversing access to marketplace credit.